Estimation of seismic demands using different basic load distribution patterns in nonlinear static analysis - Vega Arana, José Miguel (2023)
Seismic demands obtained from nonlinear static analysis play an important role in performance-based design or evaluation. It has been proved that the invariant patterns of load distribution most used in this kind of analysis are not always appropriate to represent the seismic action in structures when getting into the inelastic range. This study aims to compare the structural demands obtained from nonlinear static analysis using different basic patterns of load distribution with those obtained from the rigorous nonlinear time-history analyzes, which are considered as the benchmark. Four seismic intensities were considered, as well as two structure heights. The maximum average displacement of the top of the last level obtained from the different non-linear time-history analyzes was adopted as the objective displacement in the pushover analyzes with each pattern. The results show the lack of precision that the most used load distribution patterns have in order to adequately estimate the interstory drift ratio of the higher stories. It was found that it is possible to obtain better estimates solely for the highest stories using two proposed distribution patterns. The demands obtained for the section curvatures were acceptable considering that they are quantities of very low order.